Polish-Jewish Female Writers and the Women's Emancipation Movements in the Late Nineteenth and Early Twentieth Centuries. Issue 1 (1st June 2022) - Kołodziejska-Smagała, Zuzanna
Abstract: Between 1880 and 1914, a small group of Jewish female authors writing in Polish approached the vital-at-the-time woman question from different angles. Although they incorporated discussions of women's sexuality, for these Polish supporters of women's emancipation, access to education remained the focal point. This article explores the writings of seven Jewish women authors in the historical context of the emerging women's emancipation movements in the Polish lands, demonstrating that their educational aspirations were not always identical to those expressed by Polish emancipationists. By examining the involvement of Polish-Jewish women writers in Polish women's organizations, the article complicates the picture of the Polish suffrage movement and highlights the interconnectedness of Polish and Jewish social history.